(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Most researchers prefer to analyse the competitiveness and innovativeness of metropolitan areas. In this study we have the intention to characterize the small- and medium-sized cities in the Central and Eastern European region, as well as to explore their possible development path. We believe that one of the ways for developing these cities is to strengthen the innovation capabilities that means on one hand increasing the innovation performance of the operators, on the other hand, the new ways of interactions between other organizations to tackle social problems. The theoretical starting point is the interpretation and presentation of the micropolitan regions, as well as understanding the concept of technological and social innovation. As the result of the research, the innovation measurements carried out in some of the settlements will be represented. These experiences can help the small and medium-sized cities to be able to keep up with the global competition, cancel migration and the erosion of the intellectual potential. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.